Managing information technology's organisational impact - Clarke, Roger ed. (North-Holland AmsterdamNL, 1991)
Discusses particular aspects of contemporary information technology (IT). Offers an introduction to the nature and purposes of Electronic Data Interchange (EDI). Discusses the concepts and methods involved in assessing IT's impact. Considers some of the opportunities which are being grasped by many organisations to re-define their mission, their objectives, or their means of achieving them. Presents various aspects of the argument for a 'revised sequence' whereby technology should not be the driving force, but instead should be shaped to fit the primary needs of human organisations. Addresses specific problems which arise in the practice of IT within organisations. Deals with applications of IT at all levels of Government.